Sealant film, laminate, package, lid material, container, and food package

A sealant film with a propylene-based base layer and ethylene-based sealant layer addresses low-temperature sealing and contaminant sealing issues, ensuring effective packaging and recyclability.

JP2024176423APending Publication Date: 2024-12-19MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023094941
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing sealant films based on propylene polymers have poor low-temperature sealing properties and are less effective at sealing contaminants, limiting their recyclability and applicability in packaging.

Method used

A sealant film with a base layer composed of a propylene polymer and a sealant layer made of ethylene polymer, specifically formulated to have a predetermined density and composition, enhancing low-temperature sealing and contaminant sealing properties while maintaining recyclability.

Benefits of technology

The film achieves excellent low-temperature sealing strength, effective contaminant sealing, and high recyclability, making it suitable for various packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176423000001
    Figure 2024176423000001
  • Figure 2024176423000002
    Figure 2024176423000002
Patent Text Reader

Abstract

To provide a sealant film with superior recyclability, low-temperature sealability, and contaminant sealability, and a laminate including the sealant film, and a package such as a packaging bag and a lid material, prepared using the laminate.SOLUTION: A sealant film includes a substrate layer, and a sealant layer formed on one side or both sides of the substrate layer. The substrate layer is composed of a resin composition containing a propylene polymer (A) with a density of 900-920 kg / m3. The sealant layer is composed of a resin composition containing an ethylenic polymer (B) and a propylene polymer (C) with a density of 860-899 kg / m3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant film, a laminate, a packaging material, a lid material, a container, and a food packaging material. [Background technology]

[0002] As a packaging material, a laminate including a base film and a sealant film is known. For example, Patent Document 1 describes a laminate including a biaxially oriented polyethylene terephthalate (PET) film as the base film and a polyolefin film such as polyethylene (PE) or polypropylene (PP) as the sealant film.

[0003] On the other hand, from the viewpoint of reducing the environmental load, packaging materials with high recyclability are required. For recycling, plastic materials are required to be so-called monomaterials, which are composed of a single type of polymer. Among them, PE monomaterial packaging composed of a base film and a sealant film mainly composed of an ethylene-based polymer, or PP monomaterial packaging composed of a base film and a sealant film mainly composed of a propylene-based polymer, are preferred from the viewpoint of heat sealability.

[0004] However, while a sealant film mainly composed of a propylene-based polymer has high heat seal strength and is widely used as a film for heat sealing, it is inferior in low-temperature sealing property and sealing property against impurities compared to a film mainly composed of an ethylene-based polymer, and a solution to this problem has been sought. For example, Patent Document 2 discloses a laminate having excellent heat sealability, in which an ethylene-based polymer is used in the sealant layer of a propylene-based multilayer film. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-178357 A [Patent Document 2] Japanese Patent Application Publication No. 10-58581 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the sealant film having the configuration described in Patent Document 2 has poor heat seal strength and is limited in the contents (impurities) that can be packaged.

[0007] An object of the present invention is to provide a sealant film that is excellent in recyclability, low-temperature sealing property, and impurity sealing property, as well as a laminate using the sealant film, and a package such as a packaging bag or a lidded container using the laminate. [Means for solving the problem]

[0008] The present invention relates to the following items [1] to

[11] . [1] A sealant film having a base layer and a sealant layer formed on one or both sides of the base layer, The base layer has a density of 900 to 920 kg / m 3 The resin composition comprises a propylene-based polymer (A) having the formula: The sealant layer is made of an ethylene-based polymer (B) and a polymer having a density of 860 to 899 kg / m 3 and a propylene-based polymer (C) comprising the resin composition.

[0009] [2] The sealant film according to [1], wherein the propylene-based polymer (C) in the sealant layer is one or more propylene-α-olefin copolymers selected from the group consisting of propylene-ethylene copolymers and propylene-1-butene copolymers.

[0010] [3] The sealant film according to [1], wherein the propylene-based polymer (C) in the sealant layer contains a propylene-ethylene-α-olefin copolymer that satisfies the following requirements (b1) and (b2): Requirement (b1): The melting point measured by DSC is less than 120°C or no melting point is observed; Requirement (b2): Contains 51 to 90 mol % of structural units derived from propylene, 7 to 24 mol % of structural units derived from ethylene, and 3 to 25 mol % of structural units derived from an α-olefin having 4 to 20 carbon atoms (here, the total of the structural units derived from propylene, the structural units derived from ethylene, and the structural units derived from an α-olefin having 4 to 20 carbon atoms is 100 mol %).

[0011] [4] A laminate comprising the sealant film according to any one of [1] to [3] and a base film.

[0012] [5] The laminate according to [4], wherein the base film is a stretched propylene film.

[0013] [6] The laminate according to [5], wherein the content of the propylene-based polymer component in the laminate is 80 mass % or more.

[0014] [7] The laminate according to any one of [4] to [6], further comprising at least one functional layer selected from a printing layer, a barrier layer and an embossed layer, and the functional layer is adjacent to or in contact with at least one film selected from the base film and the sealant film via an adhesive layer.

[0015] [8] A package comprising the sealant film according to any one of [1] to [3] or the laminate according to any one of [4] to [7].

[0016] [9] The sealant film according to any one of [1] to [3] or the laminate according to any one of [4] to [7] is used as a lid material.

[0017]

[10] A container having a lid material according to [9].

[0018]

[11] A food packaging body comprising the sealant film according to any one of [1] to [3] or the laminate according to any one of [4] to [7]. Effect of the Invention

[0019] The sealant film of the present invention has excellent low-temperature sealing properties and sealing properties against foreign matter by using a resin composition containing a propylene-based polymer having a predetermined density for the base layer and a resin composition containing a specific ethylene-based polymer and a propylene-based polymer in a predetermined ratio for the sealant layer. In addition, the sealant film of the present invention is a mono-material polyolefin film mainly composed of a single type of polymer (e.g., propylene-based polymer (PP)), and therefore has excellent recyclability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] [Sealant film] The sealant film of the present invention has a base layer and a sealant layer formed on one or both sides of the base layer. The sealant layer is a layer that imparts thermal adhesion to a laminate described later, and the base layer is a layer that supports the sealant layer.

[0021] ≪Base material layer≫ The base layer used in the sealant film of the present invention has a density of 900 to 920 kg / m 3 The resin composition comprises a propylene-based polymer (A) which is one kind of the propylene-based polymer (A) or two or more kinds of the propylene-based polymer (A) may be used.

[0022] <Propylene-based polymer (A)> The propylene polymer (A) contains more than 50 mol % of structural units derived from propylene, and examples thereof include a propylene homopolymer; and a copolymer (propylene-α-olefin copolymer) of propylene and at least one α-olefin having 2 or more carbon atoms, preferably 2 to 20 carbon atoms (excluding propylene), or a diene compound.

[0023] When the propylene polymer (A) is a copolymer, it may be a random copolymer or a block copolymer, and specific examples of the copolymer include propylene-α-olefin copolymers such as propylene-ethylene copolymer, propylene-1-butene copolymer, and propylene-ethylene-1-butene copolymer. The content of the constituent units derived from the α-olefin in these copolymers is preferably 0.1 to 15 mol %, more preferably 0.5 to 10 mol %, provided that the total of the content of the constituent units derived from propylene and the content of the constituent units derived from the α-olefin is 100 mol %.

[0024] The density of the propylene copolymer (A) (in accordance with ASTM D1505) is 900 to 920 kg / m 3 , preferably 903 to 918 kg / m 3 , more preferably 905 to 915 kg / m 3 When the density is equal to or more than the lower limit, the rigidity and heat resistance of the base material layer are improved.

[0025] The melt flow rate (MFR) of the propylene polymer (A) measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg is preferably 0.1 to 30 g / 10 min, more preferably 0.5 to 20 g / 10 min. By using the propylene polymer (A) having an MFR within the above range, the fluidity of the resin or resin composition is improved, and even a relatively large film can be easily molded.

[0026] The melting point (Tm) of the propylene polymer (A) measured by differential scanning calorimetry (DSC) is preferably 120 to 165° C., more preferably 135 to 165° C. By using the propylene polymer (A) having a melting point within the above range, the moldability of the base layer can be improved, and the base layer can be provided with heat resistance and transparency.

[0027] The melting point (Tm) of the propylene-based polymer (A) is a value measured by the reheating method. Specifically, using a differential scanning calorimeter (e.g., DSC manufactured by Seiko Instruments Inc.), about 10 mg of a sample is packed in a measurement aluminum pan under a nitrogen atmosphere (20 mL / min), and the sample is heated to 200°C at 100°C / min and held for 5 minutes, then cooled to -100°C at 10°C / min, and then heated to 200°C at 10°C / min. The temperature at the peak of the crystal melting peak at this time is taken as the melting point (Tm) of the polymer. When multiple peaks are detected, the peak detected on the highest temperature side is adopted.

[0028] The propylene polymer (A) can be produced by polymerizing a monomer in the presence of a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a known polymerization method such as a gas phase method, a bulk method or a slurry method. The monomers used (propylene, α-olefins, etc.) may be derived from biomass or fossil fuels, or both may be used.

[0029] In addition to the propylene polymer (A), the base layer may contain additives, such as a resin other than the propylene polymer (A), a tackifier, a weather stabilizer, a heat stabilizer, an antistatic agent, a slip agent, an antiblocking agent, a lubricant, a pigment, a dye, a plasticizer, an antioxidant, a hydrochloric acid absorber, and an antioxidant, as necessary, within the scope of not impairing the effects of the present invention.

[0030] <Sealant layer> The sealant layer used in the sealant film of the present invention comprises an ethylene-based polymer (B) and a cellulose acylate having a density of 860 to 899 kg / m 3 and a propylene-based polymer (C) comprising the resin composition.

[0031] The resin composition constituting the sealant layer contains preferably 50 to 97 mass %, more preferably 60 to 95 mass %, of an ethylene-based polymer (B), and preferably 3 to 50 mass %, more preferably 5 to 40 mass %, of a propylene-based polymer (C) (the total content of the ethylene-based polymer (B) and the propylene-based polymer (C) is 100 mass %). When the content of each component is within the above range, a sealant film having excellent low-temperature sealability and sufficient heat seal strength can be produced.

[0032] <Ethylene-based polymer (B)> The ethylene-based polymer (B) contains more than 50 mol % of structural units derived from ethylene, and examples thereof include ethylene homopolymers; copolymers of ethylene and at least one α-olefin having 3 or more carbon atoms, preferably 3 to 20 carbon atoms (ethylene-α-olefin copolymers); ethylene-vinyl acetate copolymers, saponified products thereof, and ionomers thereof.

[0033] Specific examples of the ethylene polymer (B) include ethylene-α-olefin copolymers such as linear low-density polyethylene, branched low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-pentene copolymers, ethylene-1-hexene copolymers, ethylene-4-methyl-1-pentene copolymers, and ethylene-1-octene copolymers, of which linear low-density polyethylene and ethylene-α-olefin copolymers are preferred.

[0034] When the ethylene-based polymer (B) is a copolymer, the content of the structural units derived from the α-olefin in the copolymer is preferably 0.1 to 15 mol %, more preferably 0.5 to 12 mol %, provided that the total of the content of the structural units derived from ethylene and the content of the structural units derived from the α-olefin is 100 mol %.

[0035] The proportion of structural units derived from ethylene in the ethylene-based polymer (B) is more than 50 mol %, and in this respect the ethylene-based polymer (B) is distinguished from the propylene-based polymer (A) and the propylene-based polymer (C) described below. The ethylene polymer (B) may be of one type or of two or more types.

[0036] The density (ASTM D1505) of the ethylene polymer (B) is preferably 870 to 960 kg / m 3 , more preferably 875 to 940 kg / m 3 , more preferably 880 to 930 kg / m 3 When the density is equal to or more than the lower limit, the surface properties such as slip property and blocking property tend to be improved. When the density is equal to or less than the upper limit, the low-temperature sealability tends to be improved.

[0037] The MFR of the ethylene polymer (B) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is preferably 0.1 to 15 g / 10 min, more preferably 0.5 to 10 g / 10 min, and further preferably 1.0 to 5.0 g / 10 min. When the MFR is within the above range, molding can be performed at a high molding speed using an existing molding machine, and molding stability is improved.

[0038] The melting point (Tm) of the ethylene polymer (B) measured by DSC is preferably 60 to 165° C., more preferably 100 to 135° C., and further preferably 105 to 125° C. By using the ethylene polymer (B) having a melting point within the above range, the molding stability of the sealant layer is improved.

[0039] As the ethylene-based copolymer (B), an ethylene-based resin composition consisting of two or more ethylene-based copolymers may be used as long as the melting point (Tm) is within the above range. That is, even if the two or more ethylene-based copolymers contained in the sealant layer include one having a melting point (Tm) outside the above range, when they are mixed to prepare an ethylene-based resin composition, the resin composition is classified as the ethylene-based copolymer (B) as long as the melting point (Tm) of the resin composition is within the above range. In this case, the ethylene copolymer may be the same as the copolymers listed as specific examples of the ethylene copolymer (B).

[0040] The melting point (Tm) of the ethylene polymer (B) is a value measured by the reheating method. Specifically, using a differential scanning calorimeter (e.g., DSC manufactured by Seiko Instruments Inc.), about 10 mg of a sample is packed in a measurement aluminum pan under a nitrogen atmosphere (20 mL / min), and the sample is heated to 200°C at 100°C / min and held for 5 minutes, then cooled to -100°C at 10°C / min, and then heated to 200°C at 10°C / min. The temperature at the peak of the crystal melting peak when the sample is heated is taken as the melting point (Tm) of the polymer. When multiple peaks are detected, the peak detected on the highest temperature side is adopted.

[0041] The ethylene polymer (B) can be produced by copolymerizing ethylene and an α-olefin in the presence of a conventionally known catalyst, including a multi-site catalyst such as a Ziegler catalyst, or a single-site catalyst such as a metallocene catalyst, by a known polymerization method, such as a gas phase method, a solution method, a bulk method, or a slurry method.

[0042] The α-olefin is an α-olefin having 3 or more carbon atoms, preferably 3 to 20 carbon atoms, and examples thereof include propylene, 1-butene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, and 4,4-dimethyl-1-hexene. These may be used alone or in combination of two or more. The monomers used (ethylene and α-olefins) may be derived from biomass or from fossil fuels, or both may be used.

[0043] <Propylene-based polymer (C)> The propylene polymer (C) contains more than 50 mol % of structural units derived from propylene, and examples thereof include a propylene homopolymer and a copolymer (propylene-α-olefin copolymer) of propylene and at least one α-olefin having 2 or more carbon atoms, preferably 2 to 20 carbon atoms (excluding propylene).

[0044] When the propylene-based polymer (C) is a copolymer, it may be a random copolymer or a block copolymer. Preferable examples of the copolymer include propylene-α-olefin copolymers such as propylene-ethylene copolymer, propylene-1-butene copolymer, and propylene-ethylene-1-butene copolymer. These copolymers have excellent flexibility and can improve the interlayer strength between the base layer and the sealant layer. The content of the structural units derived from the α-olefin in these copolymers is preferably 10 to 49 mol %, more preferably 11 to 35 mol %, provided that the sum of the content of the structural units derived from propylene and the content of the structural units derived from the α-olefin is taken to be 100 mol %.

[0045] The proportion of structural units derived from propylene in the propylene-based polymer (C) is more than 50 mol %, and in this respect, the propylene-based polymer (C) is distinguished from the ethylene-based polymer (B). The propylene polymer (C) may be of one type or of two or more types.

[0046] The density of the propylene copolymer (C) (ASTM D1505) is 860 to 899 kg / m 3 , preferably 860 to 895 kg / m 3 , more preferably 865 to 890 kg / m 3 When the density is equal to or higher than the lower limit, surface properties such as slippage and blocking tend to be improved. When the density is equal to or lower than the upper limit, low-temperature sealing properties are improved.

[0047] As the propylene-based copolymer (C), a propylene-based resin composition consisting of two or more propylene-based copolymers may be used as long as the density is within the above range. That is, even if the two or more propylene-based copolymers contained in the sealant layer include one having a density outside the above range, when they are mixed to form a propylene-based resin composition, the resin composition is classified as the propylene-based copolymer (C) as long as the density of the resin composition is within the above range. In this case, the propylene copolymer may be the same as the copolymers listed as specific examples of the propylene polymer (C).

[0048] The MFR of the propylene polymer (C) measured according to ASTM D1238 at 230°C under a load of 2.16 kg is preferably 0.1 to 15 g / 10 min, more preferably 0.5 to 15 g / 10 min. When the MFR is within the above range, molding can be performed at a high molding speed using an existing molding machine, and molding stability is improved.

[0049] The melting point (Tm) of the propylene polymer (C) measured by DSC is preferably 60 to 165° C. or no melting point is observed by DSC, more preferably 65 to 135° C. or no melting point is observed by DSC, and even more preferably 70 to 120° C. or no melting point is observed by DSC. By using the propylene polymer (C) having a melting point within the above range, the molding stability of the sealant layer is improved.

[0050] The melting point (Tm) of the propylene-based polymer (C) is a value measured by the reheating method. Specifically, using a differential scanning calorimeter (e.g., DSC manufactured by Seiko Instruments Inc.), about 10 mg of a sample is packed in a measurement aluminum pan under a nitrogen atmosphere (20 mL / min), and the sample is heated to 200°C at 100°C / min and held for 5 minutes, then cooled to -100°C at 10°C / min, and then heated to 200°C at 10°C / min. The temperature at the peak of the crystal melting peak at this time is taken as the melting point (Tm) of the polymer. When multiple peaks are detected, the peak detected on the highest temperature side is adopted.

[0051] From the viewpoints of both flexibility and compatibility with the ethylene polymer (B), the propylene polymer (C) preferably contains a terpolymer of propylene, ethylene, and an α-olefin having 4 to 20 carbon atoms (propylene-ethylene-α-olefin copolymer), and more preferably contains a propylene-ethylene-1-butene copolymer. As the α-olefin having 4 to 20 carbon atoms, 1-butene, 1-hexene, 1-octene, or 1-decene is preferred due to its easy availability, and 1-butene is particularly preferred.

[0052] When the propylene-based polymer (C) contains a propylene-ethylene-α-olefin copolymer, the propylene-ethylene-α-olefin copolymer preferably satisfies the following requirements (b1) and (b2), more preferably further satisfies the following requirements (b3) to (b5), and even more preferably further satisfies the following requirement (b6).

[0053] Requirement (b1): The melting point (Tm) measured by differential scanning calorimetry (DSC) is less than 120°C, or no melting point is observed by differential scanning calorimetry (DSC). It is preferred that the melting point (Tm) is 100° C. or lower, or that no melting point is observed. The melting point (Tm) of the propylene-ethylene-α-olefin copolymer is a value measured by a normal method. Specifically, a test specimen is conditioned at 23°C±2°C for 72 hours or more using a differential scanning calorimeter (e.g., DSC manufactured by Seiko Instruments Inc.), cooled to -40°C, and then measured at a heating rate of 10°C / min. The temperature at the top of the crystalline melting peak is taken as the melting point (Tm) of the polymer. Here, "no melting point is observed" means that no crystalline melting peak with a crystalline melting heat of 1 J / g or more is observed in the range of -150 to 200°C in DSC measurement.

[0054] Requirement (b2): Contains 51 to 90 mol % of structural units derived from propylene, 7 to 24 mol % of structural units derived from ethylene, and 3 to 25 mol % of structural units derived from an α-olefin having 4 to 20 carbon atoms (however, the total of the structural units derived from propylene, the structural units derived from ethylene, and the structural units derived from an α-olefin having 4 to 20 carbon atoms is 100 mol %). The content of each of the structural units is preferably 60 to 85 mol % of structural units derived from propylene, 10 to 20 mol % of structural units derived from ethylene, and 3 to 23 mol % of structural units derived from an α-olefin having 4 to 20 carbon atoms, and more preferably 65 to 80 mol % of structural units derived from propylene, 11 to 19 mol % of structural units derived from ethylene, and 4 to 21 mol % of structural units derived from an α-olefin having 4 to 20 carbon atoms.

[0055] Requirement (b3): ​​Shore A hardness is in the range of 20 to 90. The Shore A hardness is more preferably in the range of 23 to 85, and further preferably in the range of 25 to 80. From the viewpoint of flexibility, it is preferable that the Shore A hardness is in the above range. The Shore A hardness is a value obtained by heating and melting the propylene polymer (C) at 190 to 230°C, and then press-molding the resulting specimen at a cooling temperature of 15 to 25°C, storing the specimen in an environment of 23°C ± 2°C for 72 hours or more, and then reading the scale immediately after contact with the indenter using an A-type measuring instrument (in accordance with ASTM D2240).

[0056] Requirement (b4): The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (molecular weight distribution) measured by gel permeation chromatography (GPC) is 1.2 to 3.5. The ratio (Mw / Mn) is preferably from 1.5 to 2.9, and more preferably from 1.8 to 2.4. Such a molecular weight distribution is preferable from the viewpoint of suppressing sticky feeling due to a small amount of low molecular weight components. The weight average molecular weight (Mw) and number average molecular weight (Mn) are values ​​obtained by gel permeation chromatography (GPC) in terms of polystyrene.

[0057] Requirement(B5): 13 The isotactic triad fraction (mm) calculated by C-NMR is 85 to 99.9%. The isotactic triad fraction (mm) is preferably 85 to 97.5%, more preferably 90 to 97%. When the isotactic triad fraction (mm) is within the above range, the crystallinity is not completely lost even when a large amount of comonomer such as ethylene or 1-butene is copolymerized, which is preferable from the viewpoint of mechanical properties and the like. The isotactic triad fraction (mm) can be measured using the method described in WO 2004 / 087775, from page 21, line 7 to page 26, line 6.

[0058] Requirement (b6): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -50 to -10°C. It is preferable for the glass transition temperature (Tg) to be within the above range in terms of mechanical properties at low temperatures. The glass transition temperature (Tg) can be determined by a differential scanning calorimeter (DSC) under the conditions described in the above requirement (b1).

[0059] The propylene polymer (C) can be produced by homopolymerizing propylene or copolymerizing propylene and an α-olefin having 2 to 20 carbon atoms (excluding propylene) in the presence of a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a known polymerization method such as a gas phase method, a solution method, a bulk method or a slurry method.

[0060] Specific examples of α-olefins having 2 to 20 carbon atoms include ethylene, 1-butene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, and 4,4-dimethyl-1-hexene, etc. These may be used alone or in combination of two or more. Furthermore, the monomers (propylene and α-olefins) may be derived from biomass or from fossil fuels, or both biomass-derived and fossil fuel-derived monomers may be used.

[0061] The sealant layer may contain additives, such as a resin other than the ethylene polymer (B) and the propylene polymer (C), a tackifier, a weather stabilizer, a heat stabilizer, an antistatic agent, a slip agent, an antiblocking agent, a lubricant, a pigment, a dye, a plasticizer, an antioxidant, a hydrochloric acid absorber, and an antioxidant, as necessary, within the scope of not impairing the effects of the present invention.

[0062] <How to make sealant film> The sealant film of the present invention is a laminated film having a base layer and a sealant layer on one or both sides of the base layer, and can be obtained by directly laminating the base layer and the sealant layer. The sealant film can be formed by known methods such as cast molding and inflation molding. Specifically, the sealant film can be produced by supplying the resin composition constituting the sealant layer and the resin composition constituting the base layer to two extruders connected to a T-die, respectively, and co-extrusion molding. The temperature of the molten resin during film formation is preferably 160 to 260°C.

[0063] The thickness of the sealant film of the present invention is appropriately set depending on the application of the film, and for example, when used as a sealant film, it is preferably 3 to 100 μm. The thickness of the sealant layer in the sealant film is preferably 1 to 25 μm, and the thickness of the base layer is preferably 2 to 75 μm. When there are a plurality of sealant layers and base layers, it is preferable that the thickness of each layer is within the above range.

[0064] [Laminate] The laminate of the present invention has the above-mentioned sealant film and base film. The laminate of the present invention may have, but is not limited to, a structure such as sealant film / base film or sealant film / base film / base film. For example, when a plurality of sealant films of the present invention are used, one type may be used alone or two or more types may be used. In addition, an adhesive layer may be provided between the sealant film and the base film. In the laminate of the present invention, it is preferable that the base layer included in the sealant film is adjacent to the base film or is in contact with the base film via an adhesive layer.

[0065] <Base film> The film constituting the base film may be any known film depending on the application, and specific examples thereof include films made of polyesters such as polyethylene terephthalate and polyethylene naphthalate, polyethylene carbonate films, polyamide films made of nylon 6 and nylon 66, ethylene-vinyl alcohol copolymer films, polyvinylidene chloride films, and films made of polyolefins such as polypropylene. The substrate film may be one type alone or two or more types. The film may be a film on which an inorganic substance such as aluminum, zinc, silica, or an oxide thereof is vapor-deposited.

[0066] Among them, the preferred substrate film used in the present invention is a stretched PP film obtained by stretching a film formed from polypropylene (PP). As the stretching method, a known method for producing a stretched film can be used. Specifically, roll stretching, tenter stretching, tubular stretching, etc. can be mentioned. The stretching ratio is usually 1.5 to 20 times, preferably 2 to 15 times.

[0067] The thickness of the base film is usually 10 to 50 μm, preferably 15 to 45 μm, and when there are multiple base films, it is preferable that the thickness of each stretched film is within the above range. The total thickness of the laminate of the present invention is usually 30 to 150 μm, preferably 40 to 115 μm.

[0068] The laminate of the present invention has excellent low-temperature sealing properties and impurity sealing properties, and has sufficient heat seal strength. The heat seal strength is the peel strength (N / mm) measured when two identical laminates are stacked with the sealant layer surfaces facing each other, the lower seal bar is heated at 70°C, the upper seal bar is heated at 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C, the pressure of 0.2 MPa for 1 second with a seal bar width of 5 mm, and then cooled, and then a 15 mm wide test piece is cut from each heat-sealed test piece, and the heat-sealed part of each test piece is peeled off at a crosshead speed of 300 mm / min in the direction of 180° to the laminate surface.

[0069] The term "excellent low-temperature sealability" means that, in a state where no impurities are attached to the sealant layer of the laminate, the maximum heat seal strength of the laminate in a temperature range of 100°C to 130°C, i.e., the maximum peel strength of each test piece prepared by changing the temperature of the upper seal bar within the range of 100°C to 130°C in the above-mentioned heat seal strength measurement, is 20N / 15mm or more, preferably 22N / 15mm or more. The upper limit of the maximum heat seal strength in a temperature range of 100°C to 130°C is usually 50N / 15mm. If the maximum heat seal strength of the laminate in a temperature range of 100°C to 130°C is equal to or more than the lower limit, heat sealing at low temperatures is possible, and high-speed filling can also be accommodated.

[0070] The term "excellent impurity sealability" means that, in a state where impurities (e.g., liquids such as oil or powders such as powdered milk) are attached to the sealant layer of the laminate, the maximum heat seal strength of the laminate in a temperature range of 110°C to 140°C, i.e., the maximum peel strength of each test piece prepared by changing the temperature of the upper seal bar within the range of 110°C to 140°C in the above-mentioned heat seal strength measurement, is 16N / 15mm or more. The upper limit of the maximum heat seal strength in a temperature range of 110°C to 140°C is usually 50N / 15mm. If the maximum heat seal strength of the laminate in a temperature range of 110°C to 140°C is equal to or greater than the lower limit, heat sealing at low temperatures is possible even if impurities are attached to the sealant layer, and high-speed filling is also possible.

[0071] In the laminate film of the present invention, the propylene-based polymer component in the laminate (the propylene-based polymer contained in the sealant layer and base layer in the sealant film, and the propylene-based polymer contained in the base film, etc.) is preferably 80% by mass or more, and particularly preferably 90% by mass or more. When the propylene-based polymer component in the laminate is in the above range or more, the laminate can be said to have a PP monomaterial structure, and is excellent in recyclability. A method for calculating the propylene-based polymer component in the laminate will be described in detail in the Examples.

[0072] The laminate of the present invention may be produced by laminating a base film and a sealant film by dry lamination, non-solvent lamination, sand lamination, etc., or may be produced by laminating a base film (stretched film) and a sealant film by melt extrusion lamination. Among these, the method of laminating by dry lamination or melt extrusion lamination is preferable.

[0073] The laminate of the present invention may further have at least one functional layer selected from a printed layer, a barrier layer, and an embossed layer in order to impart a specific function to the base film and the sealant film. From the viewpoint of imparting a function to the base film and the sealant film, it is preferable that these functional layers are adjacent to the at least one film selected from the base film and the sealant film or are in contact with the at least one film selected from the base film and the sealant film via an adhesive layer. That is, the functional layer is adjacent to at least one layer selected from the base layer and the base film of the sealant film, or is in contact with the layer via an adhesive layer.

[0074] For the functional layer, a resin film on which an inorganic compound or an inorganic oxide is vapor-deposited, a metal foil, a coating film of a resin having a special function, a resin film on which a pattern is printed, or the like can be used. The resin film used here can be a polymer film similar to the polymer used in the base film, and further, similar plastic compounding agents and additives can be added in any amount depending on the purpose, as long as they do not adversely affect other performances.

[0075] The resin film can be produced, for example, by using one or more resin polymers selected from the group of resin polymers described above as the polymers used in the stretched film, and by a conventionally used film-forming method such as extrusion, cast molding, T-die method, cutting method, inflation method, etc., or by a multilayer co-extrusion film-forming method using two or more resins. Furthermore, from the viewpoint of the strength, dimensional stability, and heat resistance of the film, it can be stretched uniaxially or biaxially using, for example, a tenter method or a tubular method.

[0076] For example, when the laminate includes a barrier layer as a functional layer, it can be produced by a method similar to the method for producing a laminate, which includes a step of forming the barrier layer as a layer in the base film or sealant film by metal vapor deposition, a coating method or a coextrusion method, and a step of laminating the above-mentioned base film and sealant film layer.

[0077] [Packaging] The packaging of the present invention can be obtained from the above-mentioned sealant film or laminate of the present invention. The packaging containing the sealant film or laminate of the present invention has excellent low-temperature sealing properties and foreign matter sealing properties.

[0078] For example, a package such as a packaging bag can be produced by placing the sealant film surfaces of the laminates facing each other or facing the sealant film surface of the laminate against another film, and then heat-sealing at least a part of the periphery from the outer surface side to form a desired shape. Also, a sealed package can be produced by heat-sealing the entire periphery. The forming of the package can be combined with a filling step, i.e., the bottom and sides of the package can be heat sealed, the package can be filled, and then the top can be heat sealed to produce a filled package.

[0079] The package of the present invention is suitably used as a package (food package) for solids such as snacks, bread, instant noodles, chocolate, yokan, candy, etc.; powders such as sugar, salt, powdered seasonings, powdered milk, instant coffee, etc.; or liquids such as oil, dressing, soy sauce, miso, jelly drinks, jelly, etc., and is used, for example, in an automatic packaging device, etc. In addition, the package can also be suitably used as a package (cosmetic package) for medicines, creams, lotions, cleansing products, etc., and as a package for daily necessities such as detergents, shampoos, hand soaps, etc.

[0080] In addition, a sheet made of the sealant film or laminate of the present invention can be used to form a container into a cup shape by vacuum forming, pressure forming, injection molding, etc., or a container formed from a paper base material, etc., and then the contents can be filled into the container. The sheet made of the sealant film or laminate of the present invention can then be used to cover the container as a lid and the top or sides of the container can be heat-sealed to produce a lidded container containing the contents. The container is suitably used as a package (food package) for instant noodles, chocolate, sweet bean jelly, ice cream, jelly, pudding, snacks, etc., a package for medicines, a package for creams, etc. (cosmetic package).

[0081] When the laminate or packaging body has a mono-material structure, it can be effectively used as a recycled product. A molded product that is a recycled laminate or packaging body can reduce the amount of newly polymerized plastic used, and can be an article that can contribute to reducing the environmental load. EXAMPLES

[0082] Next, the laminate of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these. The materials used in the examples and comparative examples are shown below.

[0083] <Sealant film> <Propylene-based polymer (A)> PP (A-1): rPP (random polypropylene, MFR (230°C, 2.16 kg load, conforms to ASTM D1238): 7 g / 10 min, density (conforms to ASTM D1505): 910 kg / m 3 Melting point: 140°C, propylene content: 95 mol%, ethylene content: 1 mol%, 1-butene content: 4 mol%)

[0084] <Ethylene-based polymer (B)> PE (B-1): LLDPE (linear low-density polyethylene, MFR (190°C, 2.16 kg load, conforms to ASTM D1238): 3.8 g / 10 min, density (conforms to ASTM D1505): 913 kg / m 3 , melting point: 113℃) PE (B-2): EBR (ethylene-1-butene copolymer, MFR (190°C, 2.16 kg load) = 3.6 g / 10 min, density (based on ASTM D1505): 885 kg / m 3 Melting point: 66°C, ethylene content: 89 mol%, 1-butene content: 11 mol%)

[0085] <Propylene-based polymer (C)> PP(C-1): PBR-1 (propylene-1-butene copolymer, MFR (230℃, 2.16kg load, conforms to ASTM D1238): 7g / 10min, density (conforms to ASTM D1505): 890kg / m 3 , melting point: 75°C, propylene content: 75 mol%, 1-butene content: 25 mol%) PP(C-2): PBR-2 (propylene-1-butene copolymer, MFR (230°C, 2.16 kg load, conforming to ASTM D1238): 7g / 10min, MFR (190°C, 2.16 kg load, conforming to ASTM D1238): 3g / 10min, Density (conforming to ASTM D1505): 890kg / m 3 Melting point: 98°C, propylene content: 85 mol%, 1-butene content: 15 mol%) PP(C-3): PER(propylene-ethylene copolymer, (MFR(230℃, 2.16kg load, conforms to ASTM D1238): 8g / 10min, density(conforms to ASTM D1505): 860kg / m 3 Melting point: 75°C, Propylene content: 87 mol%, Ethylene content: 13 mol%)

[0086] PP(C-4): Propylene-based resin composition The propylene resin composition was prepared by melt-kneading 90% by mass of propylene-ethylene-1-butene copolymer (hereinafter also referred to as "PEBR") and 10% by mass of propylene homopolymer, and then pelletizing the mixture. The density of the propylene resin composition (based on ASTM D1505) was 870 kg / m 3 It was.

[0087] The PEBR used was prepared according to the method described in the Examples section of the <Third Invention> described in the pamphlet of WO 2006 / 57361, had an ethylene content of 16 mol%, a propylene content of 78 mol%, a 1-butene content of 6 mol%, no melting point (Tm) measured by a normal method was observed, the MFR (230°C, 2.16 kg load, in accordance with ASTM D1238) was 6 g / 10 min, the glass transition temperature was -21°C, the molecular weight distribution (Mw / Mn) measured by GPC was 2.0, and the Shore A hardness (in accordance with ASTM D2240) was 73, 13 The isotactic triad fraction (mm) calculated by C-NMR was 92%. The propylene homopolymer used had a melting point (Tm) of 160° C., measured by a heating-reheating method, and an MFR (230° C., 2.16 kg load, in accordance with ASTM D1238) of 7 g / 10 min.

[0088] <Base film> OP U-1 25μm (Mitsui Chemicals Tocello Co., Ltd., biaxially oriented polypropylene film), density (based on ASTM D1505): 910kg / m 3 )

[0089] The melting point, heat seal strength, heat seal strength after impurities (oil), and heat seal strength after impurities (powder) of each (co)polymer were measured by the following measurement methods.

[0090] <Melt point measurement (reheating method)> Using a differential scanning calorimeter (DSC manufactured by Seiko Instruments Inc.), approximately 10 mg of the sample was packed into a measurement aluminum pan under a nitrogen atmosphere (20 mL / min), the temperature was raised to 200°C at 100°C / min and held for 5 minutes, then cooled to -100°C at 10°C / min, and then raised to 200°C at 10°C / min. The temperature at the apex of the crystal melting peak was taken as the melting point (Tm).

[0091] <Melt point measurement (normal method)> Using a differential scanning calorimeter (DSC manufactured by Seiko Instruments Inc.), the test specimen was conditioned at 23°C ± 2°C for 72 hours or more, cooled to -40°C, and then measured at a heating rate of 10°C / min. The temperature at the apex of the crystalline melting peak was taken as the melting point (Tm) of the polymer.

[0092] <Heat seal strength measurement> Two laminates prepared in the Examples and Comparative Examples were stacked so that the sealant layer surfaces faced each other and the MD directions (the direction in which the molten resin was flowed during molding) of each sealant layer were aligned, and both outer surfaces of the stacked film were sandwiched between 50 μm-thick Teflon (registered trademark) sheets to prepare test specimens.

[0093] Next, the heat seal bar of a heat seal tester (manufactured by Tester Sangyo Co., Ltd., TP-701-G type) was set to a width of 5 mm x length of 300 mm, and the lower heat seal bar was set to 70 ° C. The upper heat seal bar was set to 100 ° C., and the test body (Teflon sheet / laminate / laminate / Teflon sheet) was sandwiched between the seal bars and heat sealed for 1.0 second at a pressure of 0.2 MPa. The Teflon sheet was removed, and the heat-sealed film portion was left at about 23 ° C. for 1 day. Thereafter, a 15 mm wide slit was made to include the heat-sealed portion of the film, and the unsealed portion was fixed to a tensile tester (manufactured by Shimadzu Corporation, EZ-X), and the peel strength of the film was measured at a speed of 300 mm / min. The above operation was performed five times, and the average value was taken as the heat seal strength. The set temperature of the upper heat seal bar was changed to 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, and 170°C, and similar experiments were conducted.

[0094] <Measurement of heat seal strength against foreign matter (oil)> A test specimen for measuring heat seal strength against foreign matter (oil) was prepared according to the following procedure. (1) Salad oil (product name "Nissin Salad Oil", manufactured by Nisshin Oillio Group, Ltd.) is applied with a brush to the sealant layer of the laminate produced in the Examples and the like. (2) Another layer of the laminate was placed between the salad oil and the laminated film, and both sides of the laminated film were sandwiched between 50 μm-thick Teflon (registered trademark) sheets to prepare a test specimen. The heat seal strength against impurities (oil) was evaluated using the same measurement method as in the above <Measurement of heat seal strength>. However, the minimum temperature setting was 110°C, and the subsequent temperatures were changed to 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C, and the same measurements were performed.

[0095] <Measurement of heat seal strength against foreign matter (powder)> A test specimen for measuring heat seal strength against impurities (powder) was prepared according to the following procedure. (1) Two samples were prepared by cutting the laminate produced in the Examples etc. to 110 mm length x 80 mm width. The two samples were stacked with the sealant layer on the inside, and one side of the longitudinal end and both sides of the lateral ends were heat-sealed over a width of 5 mm under conditions of 160°C, 0.2 MPa, and 1.0 second to produce a pouch with one side of the longitudinal end open. (2) 80 mg of creaming powder (trade name "Brite", manufactured by Nestle) was poured into the opening of the pouch. The opening was then heat-sealed over a width of 5 mm at 160°C, 0.2 MPa, and 1.0 second to hermetically seal the pouch. (3) The pouch was shaken to uniformly disperse the creaming powder inside the pouch and prepare a test specimen. The heat seal strength of impurities (powder) was evaluated using the same measurement method as in the above <Measurement of heat seal strength>. However, the minimum temperature setting was 110°C, and the subsequent temperatures were changed to 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C, and the same measurements were performed.

[0096] <Content of propylene-based polymer component in laminate (PP content)> The PP content (mass%) in the laminate was calculated using the following formula.

[0097]

number

[0098] [Example 1] Using two extruders connected to a T-die, the resin composition for the sealant layer (a resin composition obtained by blending PE (B-1) and PP (C-1) at a mass ratio of 90 / 10, respectively) and PP (A-1) for the base material layer were fed to each extruder, the die and resin temperatures were set to 230 ° C., and the extrusion amount of each extruder was adjusted to produce a sealant film in which a 50 μm-thick unstretched base material layer and a 10 μm-thick unstretched sealant layer were laminated by co-extrusion molding. Next, a 25 μm-thick base material film was laminated on the base material layer surface of the obtained sealant film via an adhesive layer by a dry lamination method to produce a laminate. Using the obtained laminate, the heat seal strength, impurity (oil) heat seal strength, and impurity (powder) heat seal strength were determined by the above-mentioned measurement method. The results are shown in Table 1.

[0099] [Examples 2 to 10, Comparative Examples 1 to 4] A laminate was produced in the same manner as in Example 1, except that the composition of the resin composition for the sealant layer was changed to the composition shown in Table 1, and the thicknesses of the base layer and sealant layer of the sealant film were changed to the thicknesses shown in Table 1. Using the obtained laminate, the heat seal strength, the heat seal strength against impurities (oil), and the heat seal strength against impurities (powder) were measured by the above-mentioned measuring methods. The results are shown in Table 1.

[0100] [Table 1]

Claims

1. A sealant film having a base layer and a sealant layer formed on one or both sides of the base layer, The base layer has a density of 900 to 920 kg / m 3 The resin composition comprises a propylene-based polymer (A) having the formula: The sealant layer is made of an ethylene-based polymer (B) and a polymer having a density of 860 to 899 kg / m 3 and a propylene-based polymer (C) comprising the resin composition.

2. 2. The sealant film according to claim 1, wherein the propylene-based polymer (C) in the sealant layer is one or more propylene-α-olefin copolymers selected from the group consisting of propylene-ethylene copolymers and propylene-1-butene copolymers.

3. The sealant film according to claim 1, wherein the propylene-based polymer (C) in the sealant layer contains a propylene-ethylene-α-olefin copolymer that satisfies the following requirements (b1) and (b2): Requirement (b1): The melting point measured by DSC is less than 120° C. or no melting point is observed; Requirement (b2): Contains 51 to 90 mol % of structural units derived from propylene, 7 to 24 mol % of structural units derived from ethylene, and 3 to 25 mol % of structural units derived from an α-olefin having 4 to 20 carbon atoms (here, the total of the structural units derived from propylene, the structural units derived from ethylene, and the structural units derived from an α-olefin having 4 to 20 carbon atoms is 100 mol %).

4. A laminate comprising the sealant film according to claim 1 and a base film.

5. The laminate according to claim 4 , wherein the base film is a stretched polypropylene film.

6. The laminate according to claim 5 , wherein the content of the propylene-based polymer component in the laminate is 80% by mass or more.

7. The laminate according to claim 4, further comprising at least one functional layer selected from a printing layer, a barrier layer and an embossed layer, the functional layer being adjacent to or in contact with at least one film selected from the base film and the sealant film via an adhesive layer.

8. A packaging body comprising the sealant film according to any one of claims 1 to 3 or the laminate according to any one of claims 4 to 7.

9. A covering material comprising the sealant film according to any one of claims 1 to 3, or the laminate according to any one of claims 4 to 7.

10. A container having the lid material according to claim 9.

11. A food packaging product comprising the sealant film according to any one of claims 1 to 3 or the laminate according to any one of claims 4 to 7.

Citation Information

Patent Citations

  • Heat shrinking multilayer film

    JP1998058581A

  • Packaging bag

    JP2017178357A